Qur’anic and GROW-Shura Based Coaching Leadership Model for Enhancing Pesantren Teacher Performance - Lutfi Aldiansyah; Akhmad Fauzi Hamzah (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2026)
Educational leadership within Islamic institutions is continuously challenged to be managerially effective while maintaining a profound spiritual anchor in facing modern disruptions. This study aims to analyze in depth the implementation of a coaching-based leadership model rooted in Qur’anic values to enhance teacher performance at PPTQ Nuzhatul Muttaqien, Citra Raya, Tangerang, Banten. Utilizing a qualitative approach with a case study design, field data were gathered through participant observation, in-depth interviews with the pesantren leadership and the teaching staff (asatidz), and institutional documentation. The data were analyzed interactively, encompassing data condensation, data display, and conclusion drawing. The results indicate that coaching leadership is effectively executed by harmonizing modern mentoring frameworks (the GROW model) with the internalization of prophetic virtues: shiddiq, amanah, tabligh, and fathanah. This model positions the principal as a learning leader who prioritizes humanistic personal approaches, moral exemplification, and the reinforcement of intrinsic motivation. The shura-based (deliberative) intervention successfully transforms the institutional cultivation from a rigid-directive pattern into an empowering dialogue, thereby reducing teacher resistance, strengthening pedagogical accountability, and elevating the professional performance of the faculty. In conclusion, the integration of Qur’anic theological aspects and modern management tactics creates a holistic, blessed, and sustainable human resource management paradigm within the pesantren environment.